Conceived global: A new breed of portuguese explorer - Miranda, Pedro Miguel da Silva (2014)
Since the concept of the Born Global was defined in 1993 there have been an extensive number of research papers and articles on this subject. Despite the large amount of research conducted in this area, we have found no clear evidence of papers studying the impact of the planning stage and of business model definition on the success of the internationalization process. For this study we make use of Portuguese Born Global companies and try to determine how the founders‘ initial planning, dynamic capabilities and networks contribute to shaping BGs‘ evolution and early internationalization patterns. Based on the case studies evidence we conclude that neither a detailed business plan nor external financial support are indispensable conditions for successful internationalization. Instead, the evidence clearly shows that the entrepreneur‘s networks and dynamic capabilities together with the companies‘ adaptability to market unpredictability are the necessary conditions for a Born Global to be successful at the global stage.